Binding between the Niemann–Pick C1 protein and a photoactivatable cholesterol analog requires a functional sterol-sensing domain - Ohgami, Nobutaka (National Academy of Sciences, 2004)
Niemann–Pick type C (NPC) 1 protein plays important roles in moving cholesterol and other lipids out of late endosomes by means of vesicular trafficking, but it is not known whether NPC1 directly interacts with cholesterol. We performed photoaffinity labeling of intact cells expressing fluorescent protein (FP)-tagged NPC1 by using [(3)H]7,7-azocholestanol ([(3)H]AC). After immunoprecipitation, (3)H-labled NPC1-GFP appeared as a single band. Including excess unlabeled sterol to the labeling reaction significantly diminished the labeling. Altering the NPC1 sterol-sensing domain (SSD) with loss-of-function mutations (P692S and Y635C) severely reduced the extent of labeling. To further demonstrate the specificity of labeling, we show that NPC2, a late endosomal/lysosomal protein that binds to cholesterol with high affinity, is labeled, whereas mutant NPC2 proteins inactive in binding cholesterol are not. Vamp7, an abundant late endosomal membrane protein without an SSD but with one transmembrane domain, cannot be labeled. Binding between [(3)H]AC and NPC1 does not require NPC2. Treating cells with either U-18666A, a compound that creates an NPC-like phenotype, or with bafilomycin A1, a compound that raises late endosomal pH, has no effect on labeling of NPC1-YFP, suggesting that both drugs affect processes other than NPC1 binding to cholesterol. We also developed a procedure to label the NPC1-YFP by [(3)H]AC in vitro and showed that cholesterol is more effective in protection against labeling than its analogs epicholesterol or 5-α-cholestan. Overall, the results demonstrate that there is direct binding between NPC1 and azocholestanol; the binding does not require NPC2 but requires a functional SSD within NPC1.